PERAN SISTEM PENJAMINAN MUTU PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH - Khoirul Anwar (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2018)
The quality of education is related to whether or not national education goals are achieved as stated in Law No. 20 of 2003 concerning the National Education System. Therefore, the quality of education can be said it is good if it meets the National Education Standards. The fulfillment of minimum standards of education which is the National Standard of Education is a prerequisite to improve the quality of education including madrasah. The reality that emerges is the quality of education in Indonesia is still far from what is expected, let a quality in most madrasah which are still having many obstacles. Many madrasah do not qualify the National Education Standards, such as educators and education staff who have not met standardized qualifications and competencies, and inadequate facilities and infrastructure. This paper aims to describe how the role of the education quality assurance system in improving the quality of education in madrasah.